A new animal model for delayed osseous union secondary to osteitis - Helbig, Lars; Gühring, Thorsten; Rosenberger, Svenja; Ivanova, Adriana; Käppler, Kathrin; Fischer, Christian; Moghaddam-Alvandi, Arash; Schmidmaier, Gerhard (BMC musculoskeletal disorders, 2015)
The treatment of infection-related delayed bone unions is still very challenging for the orthopedic surgeon. The prevalence of such infection-related types of osteitis is high in complex fractures, particularly in open fractures with extensive soft-tissue damage. The aim of this study was to develop a new animal model for delayed union due to osteitis.
Gesehen am 17.08.2020